Large intestinal pathology at liver cirrhoses - M. V. Safonova; I. V. Kozlova; V. V. Ovsyannikova; I. M. Kvetnoy (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To determine clinical and morphological features and some mechanisms of diseases of the large intestine in liver cirrhoses (LC).Material and methods. Overall 146 patients with LC of various classes were investigated. Clinical, endoscopic, morphological, immunehistochemical methods of study were applied.Results. Symptoms of intestinal dysfunction were revealed at 49% of patients. Endoscopic signs of portal colonopathy were diagnosed in 63% of cases. Frequency of clinical and endoscopical symptomatology of large intestinal pathology increased along with increase in LC class and was associated with hyperproduction of serotonin and chromogranin-A.Conclusions. Absence of clinical symptoms of intestinal dysfunction does not exclude endoscopic and morphological signs of lesion of the large intestine at LC. Higher frequency of inflammatory and atrophic changes of mucosa of the large intestine at progressive stages of disease is caused by disorder of production of investigated components of diffuse endocrine system.